2019
DOI: 10.1074/jbc.ra118.004397
|View full text |Cite
|
Sign up to set email alerts
|

Ribonucleotide reductase M2 promotes RNA replication of hepatitis C virus by protecting NS5B protein from hPLIC1-dependent proteasomal degradation

Abstract: Edited by Charles E. SamuelHepatitis C virus (HCV) establishes a chronic infection that can lead to cirrhosis and hepatocellular carcinoma. The HCV life cycle is closely associated with host factors that promote or restrict viral replication, the characterization of which could help to identify potential therapeutic targets. To this end, here we performed a genome-wide microarray analysis and identified ribonucleotide reductase M2 (RRM2) as a cellular factor essential for HCV replication. We found that RRM2 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…It has been found that the HBV induces RRM2 expression via activating DNA damage response and targeting RRM2 by small molecules could inhibit HBV replication [58,59]. Similarly, RRM2 is also upregulated by the HCV and promotes viral RNA replication [60]. These studies suggest that RR-or RRM2-targeting agents may serve as potential antiviral agents for HBV/HCV infection and HBV/HCV-related HCC.…”
Section: Discussionmentioning
confidence: 91%
“…It has been found that the HBV induces RRM2 expression via activating DNA damage response and targeting RRM2 by small molecules could inhibit HBV replication [58,59]. Similarly, RRM2 is also upregulated by the HCV and promotes viral RNA replication [60]. These studies suggest that RR-or RRM2-targeting agents may serve as potential antiviral agents for HBV/HCV infection and HBV/HCV-related HCC.…”
Section: Discussionmentioning
confidence: 91%
“…For example, RNRs are almost ubiquitous among large double-stranded DNA (dsDNA) viruses, such as herpesviruses, poxviruses, and tailed phages (caudovirales), presumably due to high dNTP requirements during DNA replication [35][36][37]. On the other hand, most small dsDNA viruses and single-stranded DNA viruses do not encode RNRs and instead rely on host-encoded RNRs for deoxyribonucleotide production [38,39]. In addition to ribonucleotide reductase activity, some viral RNRs have been shown to engage in non-catalytic activities that result in proviral phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Ribonucleotide reductase M2 (RRM2), a critical rate-limiting enzyme for DNA synthesis and repair, plays an important role in cell division, proliferation and differentiation by promoting cells proliferation and inhibiting cellular apoptosis. Host RRM2 and NS5B can inhibit RNA replication of hepatitis B virus, thereby inhibiting the conversion of hepatitis B to liver cancer (20). RRM2 may be a key gene for liver cancer transformation from cirrhosis via P53 pathway(21), Gao(22) suggested in his study that RRM2 was a candidate target for HCC therapy as suppression of RRM2 markedly suppressed proliferation of HCC cells and RRM2 expression was higher in HCC than in non-HCC tissue.…”
Section: Discussionmentioning
confidence: 99%